Analyse de l’ironie dans les discours politiques et conférences de presse de Vladimir Poutine - Kapeja, Nathalia (Neophilologica, 2019)
This paper analyzes the different types of irony used by Russian President Vladimir Putin during his official and less formal appearances. The analysis will focus on the Russian President’s speeches during the G8 meeting, during the first diplomatic meeting with President Nicolas Sarkozy at the St. Petersburg Economic Forum, during “A Grown-up conversation” with Vladimir Putin organized in Sochi, at the press conference following the BRICS summit in China, at a press conference in Moscow, in the Kremlin, during the intervention in the economic forum, and at the press conference in St. Petersburg. This paper will prove that the Russian president likes to joke.